Extrapedicular Infiltration Anesthesia as an Improved Method of Local Anesthesia for Unipedicular Percutaneous Vertebroplasty or Percutaneous Kyphoplasty. (28th September 2016) - Liu, Liehua; Cheng, Shiming; Lu, Rui; Zhou, Qiang
Abstract : Aim. This report introduces extrapedicular infiltration anesthesia as an improved method of local anesthesia for unipedicular percutaneous vertebroplasty or percutaneous kyphoplasty. Method. From March 2015 to March 2016, 44 patients (11 males and 33 females) with osteoporotic vertebral compression fractures with a mean age of 71.4 ± 8.8 years (range: 60 to 89) received percutaneous vertebroplasty or percutaneous kyphoplasty. 24 patients were managed with conventional local infiltration anesthesia (CLIA) and 20 patients with both CLIA and extrapedicular infiltration anesthesia (EPIA). Patients evaluated intraoperative pain by means of the visual analogue score and were monitored during the procedure for additional sedative analgesia needs and for adverse nerve root effects. Results. VAS of CLIA + EPIA and CLIA group was 2.5 ± 0.7 and 4.3 ± 1.0, respectively, and there was significant difference (P = 0.001 ). In CLIA group, 1 patient required additional sedative analgesia, but in CLIA + EPIA group, no patients required that. In the two groups, no adverse nerve root effects were noted. Summary. Extrapedicular infiltration anesthesia provided good local anesthetic effects without significant complications. This method deserves further consideration for use in unipedicular percutaneous vertebroplasty and percutaneous kyphoplasty.